IMPLEMENTASI TEKNIK PEMBELAJARAN ICE BREAKING DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS X MIPA SMA PLUS MUNIRUL ARIFIN NW PRAYA - Howin Hendria Santana; Ziadatul Husna (PT. Media Akademik Publisher, 2023)
The purpose of this study was to determine the effect of ice breaking learning techniques in increasing students' learning interest. This study used a quantitative approach with a quasi-experimental design type of experimental research and used a nonequivalent control group. The population for this study were all of class X MIPA 1 and MIPA 2 with a total of 44 students. As for the sample, class X MIPA 1 as the experimental class and X MIPA 2 as the control class. The data collection technique was carried out by researchers by distributing interest in learning questionnaires to students which were distributed 2 times, namely before and after the application of the ice breaking learning technique. The results of the questionnaire validation test are all valid statements (r_count>= 0.297. ). Furthermore, the results of the instrument reliability test obtained Cronbach's alpha of 0.885 and belonged to the high reliability category. The results for the t test results obtained t-count > dat t-table ((5.517 > 2.021). Thus the expected hypothesis Ha is accepted, therefore it can be concluded that the ice breaking learning technique has an effect on increasing students' interest in learning mathematics Class X MIPA 1 Plus Munirul Arifin NW Praya Academic Year 2022/2023